Unexpected Malignant Diagnosis in Colonic Biopsies: Malignant Transformation of Ovarian Mature Teratomas—Two Case Reports and Review of the Literature - Claudia P. Rojas; Parvin Ganjei-Azar; Monica T. Garcia-Buitrago (Case Reports in Pathology)
Colorectal adenocarcinoma is the second cause of cancer-related deaths in the United States. The occurrence of squamous cell carcinoma in the colorectum is extremely unusual. Malignant transformation from mature cystic teratoma of the ovary is a rare event. The most common transformation is squamous cell carcinoma, followed by adenocarcinoma. It occurs more often in elderly patients, who usually present with advance disease. We report two unusual cases of postmenopausal women diagnosed with squamous cell carcinoma in colon biopsies. After surgical resections, the carcinoma was proven to be the result of malignant transformation of ovarian mature cystic teratomas. Since squamous cell carcinoma of the colorectum is extremely rare, the presence of squamous cell carcinoma in a colonic biopsy in a female patient should alert the clinicians to other possible primary sites, as seen in these cases.